Adverse childhood experiences mediate the negative association between borderline personality disorder symptoms and plasma oxytocin - Mielke, Emilia Louisa L.; Koenig, Julian; Herpertz, Sabine; Steinmann, Sylvia; Neukel, Corinne; Kilavuz, Pelin; Venne, Patrice van der; Bertsch, Katja; Kaess, Michael (Progress in neuro-psychopharmacology & biological psychiatry, 2023)
Background Interpersonal dysfunction is a core symptom of borderline personality disorder (BPD) and may be closely linked to adverse childhood experiences. According to a recent model on the pathology of BPD, the neuropeptide oxytocin might play an important role in the development and maintenance of the disorder. However, so far, only few studies with small adult samples have reported reduced baseline oxytocin levels in BPD that may be linked to adverse childhood experiences. Methods We examined baseline plasma oxytocin levels in 131 female patients with BPD and 124 non-BPD female controls across a large age span (12-50 years). Additionally, 113 female patients with less than five DSM-IV BPD features were included to examine the association between plasma oxytocin levels and the number of fulfilled BPD criteria. We also explored associations between plasma oxytocin and adverse childhood experiences as well as depressive symptoms in BPD. Results Patients with BPD had reduced plasma oxytocin levels compared to non-BPD controls and this was independent of age. Plasma oxytocin was negatively associated with the number of fulfilled BPD criteria. The exploratory regression model revealed no association between plasma oxytocin and depressive symptoms but an association between plasma oxytocin and adverse childhood experiences, which in fact mediated the relationship between BPD criteria und plasma oxytocin. Conclusion In a large sample of individuals with BPD across a large age span, our results replicate and extend previous reports of reduced plasma oxytocin levels that might be related to adverse childhood experiences thus providing further evidence for a prominent role of oxytocin in BPD.